MANTRA PADA KOLEKSI NASKAH MERAPI-MERBABU - Kartika Setyawati (Humaniora, 2006)
Mantra may be defined as words full of power. It may be expressed both through words and letters/characters. When expressed through words, it is called mantraksara. As found in Merapi-Merbabu manuscripts, everybody can say or us mantra depending on his or her goals. Mantra is considered a secret and is passed along from one to another in a secret way. Mantra may be used for the purpose of gaining physical and sexual power, obtaining sympathy, love and pity healing sickness, and informing the spirit for various reasons.